Do European Nations have Different Issues When it Comes to Rural Development? EU Rural Leaders' Perspectives on Social and Economic Contexts - Bonifacio (Global Journal of Food and Agribusiness Management, 2024)
In Europe, rural development has grown to be a major policy concern. Rural areas are continuously declining in terms of both population and economic growth as a result of the concentration of more job opportunities in urban areas. In this regard, more general social or structural policies at the European level are incorporated into rural entrepreneurial activities that benefit rural communities. In five rural regions of Europe—Croatia (Slovania), Germany (Münsterland, Saxony-Anhalt), Poland (Małopolska), and Portugal (Alto Minho)—the article's goal is to examine societal and economic issues and their creative solutions. Using a multi-case approach, this study examines the range of problems and solutions in several rural regions of Europe. The comparative analysis shows that the most important initiatives to alleviate the development issues in rural areas are: educating local communities; enhancing digital and economic infrastructure; promoting local product production and promotion; encouraging collaboration between producers and local communities; and strengthening local policy's focus on providing financial support for farms and production enterprises. In the context of creating entrepreneurship strategies in rural areas, the study's conclusions are used to formulate suggestions for rural policies.